KOMPOSISI JENIS DAN CADANGAN KARBON DI HUTAN TROPIS DATARAN RENDAH, ULU GADUT, SUMATERA BARAT - Adi Bejo Suwardi; Erizal Mukhtar; Syamsuardi Syamsuardi (Research Center for Biology-Indonesian Institute of Sciences, 2013)
Tropical lowland forest is one type of forest ecosystem that dominated most of Sumatra areal and retained carbon terrestrial within.Tropical lowland forest has the highest risk of damage than other forest types. The aimed of study is to determine species composition and carbon stock in tropical lowland forest, Ulu Gadut, West Sumatra. This study was conducted on June to October 2012 at 1 ha Pinang-Pinang permanent plot. Tree biomass was measured by using the non destructive sampling method. All trees with stem diameter at breast height (dbh) = 8 cm were measured diameter and were recorded the species of trees.As much as 852 individuals of trees, which were consisting of 45 families and 155 species with DBH = 8 cm were found in Pinang-Pinang permanent plot. Nephelium juglandifolium Blume, Swintonia schwenckii (T. & B.) Kurz,Syzygium sp.,Microcos florida (Miq.) Burret, Palaquium sp.,Cleistanthus glandulosus Jabl., Hopea dryobalanoides Miq., Mastixia trichotoma Blume, Calophyllum soulattri Burm. f. and Shorea maxiwelliana King were dominant based on -1 -1 Importance Value Index(IVI). Trees biomass and carbon stock in the study site are around 482.75 ton ha and 241.38 ton C ha respectively.